Computer assisted language learning (CALL): its application and relevance in Malaysian public universities / Wan Zumusni Wan Mustapha - Wan Mustapha, Wan Zumusni (2023)
As Malaysia progresses in the 21st century, Malaysian English Language teachers are yet to face new challenges in their teaching profession as computers are paving their ways into their classrooms. Over the. years, CALL, E-learning and Smart School paint a new picture of Malaysian education system. It is undeniable that in the near future learning via computer or Computer Assisted Language Learning (CALL) will be an indispensable and inevitable part of the language teaching and learning methodology as this technology gains its popularity into English language classrooms in Malaysia and brings about changes in the way teachers think and teach. With the profound impact of globalization and industrialization, teachers are awaken with the challenge in preparing students who are going to survive in the new millennium that demands high level of computer literacy, making learning incomplete without complemented by lessons via computer. Integrating CALL into a Language classroom is not merely setting up the physical infrastructure, but integrating CALL into a lesson in· a more meaningful and productive way for both teachers and learners. This small-scale research addresses the issues and challenges in integrating CALL in Malaysian Language classroom at tertiary level. Literature pertaining to studies on lecturers' attitude will supplement the primary data obtained from a study conducted in three local public universities. Using qualitative methods, data consist of in-depth interviews and documentation from lecturers who teach via web-based learning and key figures in CALL to paint a bird-eye view of the current scenario in Malaysian English Language classroom in a public university. Results from this research show that a lot have to be discovered on CALL applications in Malaysian public universities as different universities have different approaches, policies and ways to implement CALL. Other issues that deserve further studies include training and curriculum development.